Mirizzi Syndrome: Diagnosis and Management of a Challenging Biliary Disease - Gennaro Clemente; Andrea Tringali; Agostino M. De Rose; Elena Panettieri; Marino Murazio; Gennaro Nuzzo; Felice Giuliante (Canadian Journal of Gastroenterology and Hepatology)
Background. Mirizzi syndrome is a condition difficult to diagnose and treat, representing a particular “challenge” for the biliary surgeon. The disease can mimic cancer of the gallbladder, causing considerable diagnostic difficulties. Furthermore, it increases the risk of intraoperative biliary injury during cholecystectomy. The aim of this study is to point out some particular aspects of diagnosis and treatment of this condition. Methods. The clinical records of patients with Mirizzi syndrome, treated in the last five years, were reviewed. Clinical data, cholangiograms, preoperative diagnosis, operative procedures, and early and late results were examined. Results. Eighteen consecutive patients were treated in the last five years. Presenting symptoms were jaundice, pain, and cholangitis. Preoperative diagnosis of Mirizzi syndrome was achieved in 11 patients, while 6 had a diagnosis of gallbladder cancer and 1 of Klatskin tumor. Seventeen patients underwent surgery, including cholecystectomy in 8 cases, bile duct repair over T-tube in 3 cases, and hepaticojejunostomy in 4 cases. Two cases (11.1%) of gallbladder cancer associated with the Mirizzi syndrome were incidentally found: a patient underwent right hepatectomy and another patient was unresectable. The overall morbidity rate was 16.6%. There was no postoperative mortality. An ERCP with stent insertion was required in three cases after surgery. Sixteen patients were asymptomatic at a mean distance of 24 months (range: 6-48) after surgery. Conclusions. Mirizzi syndrome requires being treated by an experienced biliary surgeon after a careful assessment of the local situation and anatomy. The preoperative placement of a stent via ERCP can simplify the surgical procedure.